Instagram As A Political Communication Strategy In The PKS Regional Management Council (DPD) In Pontianak City - Hadi, Marwan; Poernomo, Marlinda Irwanti (Jurnal Ilmu Sosial Mamangan, 2025)
Pontianak City is the capital of West Kalimantan Province. According to data from the General Elections Commission (KPU), it is known that in 2019, Pontianak City had a 24% abstention rate (abstentions) and 30% of the voters were first-time voters (KPU, 2022). Through a pre-research study, it was found that a significant number of young people in Pontianak City were apathetic and not interested in practical political activities, which became the main obstacle faced by the PKS of Pontianak City in implementing its communication strategies to the young sympathizers. It is known that the PKS Public Relations Team of Pontianak City uses Instagram as a communication tool to engage young sympathizers through social media. One way to shape aspirations and engage the young audience in Pontianak City to become sympathizers is through the implementation of effective political communication strategies to establish relationships with the general public, especially the younger generation (public relations). The Uses and Gratification theory, which explains the active nature of the audience in consuming media, can address this issue with five assumptions related to audience activity, audience satisfaction, media competence, audience motives, and media content evaluation. In terms of audience activity, media competence, and media content evaluation, it is considered quite good because young sympathizers have the goal of following the Instagram account @pkspontianak, which can offer activities directly involving young people and provide input and suggestions that can be implemented on the @pkspontianak Instagram account. However, in terms of audience satisfaction and motives, it is still considered less satisfactory. Further research can also gather data from the perspective of the external media environment of the institution in the development of communication strategies. This will lead to formulating strategies that enhance media competitiveness with other similar competitors